Cardiac amyloidosis in non‐transplant cardiac surgery. Issue 8 (16th May 2021) - Smith, Alex; Balmforth, D.; Treibel, T. A.; Lall, Kulvinder; Oo, Aung; Ambekar, Shirish
Abstract: Cardiac amyloidosis is a rare infiltrative cardiomyopathy that portends a poor prognosis. There is a growing recognition of co‐existent aortic valve stenosis and transthyretin cardiac amyloidosis, with some studies suggesting that dual pathology may be associated increased risk of complication and mortality during surgical intervention. This review aims to evaluate the available literature on non‐transplant cardiac surgical interventions in patients with cardiac amyloidosis, with particular focus on diagnosis, high surgical risk and areas of uncertainty that require further research.